2015
DOI: 10.1007/jhep09(2015)080
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement entropy through conformal interfaces in the 2D Ising model

Abstract: We consider the entanglement entropy for the 2D Ising model at the conformal fixed point in the presence of interfaces. More precisely, we investigate the situation where the two subsystems are separated by a defect line that preserves conformal invariance. Using the replica trick, we compute the entanglement entropy between the two subsystems. We observe that the entropy, just like in the case without defects, shows a logarithmic scaling behavior with respect to the size of the system. Here, the prefactor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 50 publications
7
80
2
Order By: Relevance
“…This can be done for some excited states that have a natural left-right decomposition (see [20,21,22,23]) but it would be interesting to preform it for (5.1) even in known RCFTs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This can be done for some excited states that have a natural left-right decomposition (see [20,21,22,23]) but it would be interesting to preform it for (5.1) even in known RCFTs.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(1.2) and the expression of c eff were also obtained in a two dimensional Ising CFT. 24 Most recently, quantum entanglement across a conformal interface where several CFTs join together was studied. It was found that the entanglement entropy of a single CFT i , with other CFTs as the rest, also has the generic form in Eq.(1.2).…”
Section: Cft2mentioning
confidence: 99%
“…27, analytical results of both entanglement spectrum and entanglement entropy were derived, and the result on entanglement entropy was later confirmed in a CFT calculation. 24 A series of works were then stimulated, including entanglement entropy across quantum wire junctions, 28,29 and entanglement entropy across a conformal interface in bosonic quantum chains. 30 Interestingly, in Ref.…”
Section: Cft2mentioning
confidence: 99%
“…In particular, we work out in detail the Ishibashi states corresponding to gapped edges and interfaces. The important new ingredients compared to previous works such as [7,8,9,10,11,12,13] are that we provide a careful treatment of the matching of anyon charges across the interface using tools in anyon condensation. The anyon condensation picture allows us to generalize the results to include cases with ground state degeneracies, and also to non-Abelian systems.…”
Section: Introductionmentioning
confidence: 99%